Correlation Between Chest Girth, Body Length, and Body Height on Wither Weight of Rote Sheep Ewes - Ni Made Paramita Setyani; Wilmientje Marlene Nalley; Thomas Mata Hine; Agustinus Ridlof Riwu; Kirenius Uly; Petrus Kune; Yustiany Yuliana Bette; Alvrado Bire Lawa; Simon Edison Mulik; Adyanto Nessy Banamtuan; Roni Markus Jami Riwu; Yanna Nailla Zulfa; Rut Listyadi (Journal of Tropical Animal Science and Technology, 2026)
This study aimed to analyze the relationship between linear body measurements including chest girth (CG), body length (BL), and wither height (WH) and body weight (BW) in Rote sheep ewes across different age groups to determine the most reliable predictor of body weight. The research employed a quantitative method through direct field measurements and weighing. Data collected including vital statistics (CG, BL, WH) and BW from Rote sheep ewes categorized into three age groups (I0, I2, and I4). The data were analyzed statistically using correlation coefficient (r), the coefficient of determination (R²), and bias analysis to evaluate the accuracy of weight estimation. The results revealed that chest girth exhibited the highest correlation with body weight, particularly in the I0 group (r = 0.93; R² = 86.05%), indicating a strong positive relationship and high predictive accuracy. Body length showed a moderate relationship (r = 0.87; R² = 76.11%) in the same group, while wither height demonstrated a relatively weaker correlation (r = 0.73; R² = 53.94%). Across all age groups, the predictive strength of body measurements decreased with increasing age, suggesting that skeletal growth contributes less to body weight variation in mature sheep. In conclusion, chest girth was identified as the most accurate and reliable linear measurement for predicting body weight in Rote sheep ewes, particularly in younger age groups, and can therefore be used as a practical and non-invasive tool for estimating livestock weight.